2002
DOI: 10.1161/01.cir.0000014413.91312.ef
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of the LDL Receptor Family Member LR11 Increases Migration of Smooth Muscle Cells In Vitro

Abstract: Background-LR11, a member of the LDL receptor family, is highly expressed in vascular smooth muscle cells (SMCs) of the hyperplastic intima but not media. To further clarify the involvement of LR11 in the process of atherosclerosis, we have characterized the migration and invasion activities of LR11-overexpressing SMCs. Methods and Results-LR11 cDNA was transfected into the rat SMC line A7r5. Compared with mock cells (C-1), in the presence of platelet-derived growth factor-BB, the transfected cells (R-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 32 publications
2
54
0
3
Order By: Relevance
“…Interestingly, previous studies have shown that uPAR expression is induced by hypoxia in cultured hematological cells (19). Furthermore, using uPARdeficient mice, Tjwa et al reported that membrane-anchored uPAR regulates HSPC adhesion and BM engraftment (17), and we have shown that sLR11 binds to and co-localizes with uPAR on the cell surface of SMCs (41). On the basis of these findings, we now demonstrate that the hypoxia-induced increase in LR11 was accompanied by an elevated level of uPAR, which FIGURE 6.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Interestingly, previous studies have shown that uPAR expression is induced by hypoxia in cultured hematological cells (19). Furthermore, using uPARdeficient mice, Tjwa et al reported that membrane-anchored uPAR regulates HSPC adhesion and BM engraftment (17), and we have shown that sLR11 binds to and co-localizes with uPAR on the cell surface of SMCs (41). On the basis of these findings, we now demonstrate that the hypoxia-induced increase in LR11 was accompanied by an elevated level of uPAR, which FIGURE 6.…”
Section: Discussionmentioning
confidence: 51%
“…In this context, we showed previously that sLR11 derived from the cell surface enhances cell adhesion through the activation of uPAR and integrin-mediated signals (21,41,42). On the other hand, LR11 in intracellular vesicles (SorLA) is important for the intracellular traffic of amyloid␤ protein in neurons (43), and single nucleotide polymorphisms in the LR11/SORL1 gene and/or sLR11 levels in the cerebrospinal fluid have been reported to be a prospective marker of Alzheimer disease (44,45).…”
Section: Discussionmentioning
confidence: 98%
“…Zhu et al observed overexpression of LDL receptors in smooth muscle cells of the hyperplastic intima. 15 Reduction of toxicity of chemotherapeutic agents by associating them to LDE was confirmed at clinical level. In trials enrolling patients with advanced cancers treated with LDE-carmustine, 10 LDE-paclitaxel, 16 and LDE-etoposide, 17 the toxicity of high-dose treatments was minimal or absent.…”
mentioning
confidence: 91%
“…Thus, Sortilin may be part of the machinery that governs cell survival in developing neuronal tissue and a key determinant in the induction of post-traumatic neuronal apoptosis (11), whereas SorLA seems implicated in the generation of Alzheimer's disease (12) as well as in atherosclerotic plaque formation (13,14). Information at the molecular and cellular level confirms that the receptors are multifunctional, bind several different ligands, and they engage in intracellular sorting as well as in endocytosis and signal transduction.…”
mentioning
confidence: 97%